Simple Mortar Mixture Proportioning Method for Meeting Minimum and Maximum Flow and Strength Requirements - Riding, Kyle A.; Peterman, Robert J.; Polydorou, Thomaida; Ren, GengFeng (My University, 2012)
The standard test for strand bond (STSB) test method has been developed to provide an assessment of the ability of steel prestressing strand to bond with cementitious materials. The test method is performed by pulling on a steel strand embedded in a 5 in. diameter steel can filled with mortar. The pullout strength is measured as the force at 0.1 in. displacement of the untensioned strand end. The test method currently requires the pullout test to be performed when the mortar has a compressive strength between 4500 and 5000 psi and between 22 and 26 hours after mixing. The mortar must also have a flow between 100 and 125 percent. It can be very difficult for laboratories to develop a mortar mixture that meets these stringent requirements with their local cement. This paper presents a simple methodology to develop mortar mixtures that meet these requirements.
Keywords: Mortar Proportioning; Strength; Flow